Evaluation of Documentation System in Iraqi Construction Projects - Hamsa R. Majeed; Wadhah A. Hatem; Nidal A. Jasem (Diyala Journal of Engineering Sciences, 2021)
In Iraq, the construction industry is considered one of the main sectors that contribute strongly to the Iraqi economy. Documentation is a process of collecting documents from past and current works of corporations, then archiving and classification of information to become easy and useful for reuse in the future. The aim of this study is to investigate the reality of documentation in the Iraqi construction industry and how to improve archiving and classification of documents and how documentation can be useful used in contractor and consultant corporations. This research has been conducted through literature reviews followed by a field survey. 80 questionnaires were distributed to contractors and engineering offices. 70 useful questionnaires were received from respondents with an 87% response rate. The findings indicated that the construction projects in the Diyala governorate are applying documentation. The study found that foundations classified and updating the documents as printed and written files and computer files, but foundations lack computer programs and web models for easy archiving and discovery of documents, documentation system currently used doesn't prevent Confusing, conflict in schemas because they still used Auto CAD and paper documentation.  The large number and accumulation of paper documents are also considered the most often problem in the documentation system currently used, and construction projects don't have a database for all information related to projects where, it is limited to cabinets full of paper documents, which causes a waste of time and effort when searching for any document or information related to the projects. The study recommended that companies and foundations have to increase cost and effort consumed in the documentation process, improve the owner and staff abilities in computer and web applications, assign a key person for collection and archiving project documents, establishing an internet website for companies, or using cloud applications for storage of documents and sharing information.